2016
DOI: 10.1016/j.exphem.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Transient potential receptor melastatin-2 (Trpm2) does not influence murine MLL-AF9-driven AML leukemogenesis or in vitro response to chemotherapy

Abstract: Transient potential receptor melastatin-2 (TRPM2) is a non-selective cationic, Ca2+ permeable transmembrane pore that is preferentially expressed in cells of the myeloid lineage, and modulates signaling pathways converging onto NF-kB. This is of potential interest for AML therapy, as NF-κB signaling is emerging as a key pathway mediating drug resistance and leukemia initiating cell survival in AML, and inhibition of NF-κB signaling has been shown to be synergistic with chemotherapy. TRPM2 is overexpressed in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…This is consistent with reports in neuroblastoma 31 , T-cell ALL 40 , and gastric cancer 38 in which TRPM2 depletion reduced malignant cell survival. It differs from a report examining AML generated on a Trpm2-/-genetic background in murine hematopoietic cells induced by retroviral introduction of MLL-AF9 or BCR-ABL-GFP and NUP98-HOXA9-YFP 41 . Loss of TRPM2 in that model had no major effect on leukemogenesis or potentiation of cytotoxic therapy.…”
Section: Discussionmentioning
confidence: 63%
“…This is consistent with reports in neuroblastoma 31 , T-cell ALL 40 , and gastric cancer 38 in which TRPM2 depletion reduced malignant cell survival. It differs from a report examining AML generated on a Trpm2-/-genetic background in murine hematopoietic cells induced by retroviral introduction of MLL-AF9 or BCR-ABL-GFP and NUP98-HOXA9-YFP 41 . Loss of TRPM2 in that model had no major effect on leukemogenesis or potentiation of cytotoxic therapy.…”
Section: Discussionmentioning
confidence: 63%
“…The researchers observed that the expression of TRPM2 in AML subgroups is the higher the more differentiated AML cells are [21]. Klumpp et al demonstrated that TRPM2 plays a key role in response to DNA damage in leukemic T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM2 is a non-selective cationic, Ca 2 + _ permeable pore, and contains a unique C-terminal region exhibiting ADP-ribose (ADPR) hydrolase activity. The highest expression levels of TRPM2 are observed in the cells of neuronal origin and in the myeloid lineage [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among other things, it has been shown that TRPM2 is involved in cell migration and cell death, which are the key processes of cancer cell death [28]. The results of the studies by Zeng et al [20] showed that in non-cancerous cells, TRPM2 proteins are mainly located at the plasma membrane where they mediate sodium and calcium influx on The researchers observed that the expression of TRPM2 in AML subgroups is the higher the more differentiated AML cells are [21]. Klumpp Our results of TRPM2 gene expression presented the context of survival time of AML patients showed a statistically significant correlation: the higher TRPM2 gene expression in bone marrow cells at the time of diagnosis, the longer the mean survival time of the patients.…”
Section: Discussionmentioning
confidence: 99%